Stephen Wheel on songwriting: An interview. Issue 1 (1st April 2019) - Smith, Gareth Dylan
In this interview, Welsh guitarist, composer, producer and songwriter, Stephen Wheel discusses his reasons for writing songs, his approach to songwriting and his compulsion to make music. He talks about occupying the intersecting roles of producer, writer, engineer and performer, and the integrity of performances to a completed song. He writes for himself, being instigator and arbiter of the creative process. He describes how some songs are easier to finish than others, as he strives to complete each song on its terms. Melodies and lyrics have often been the most elusive elements of songwriting for Wheel, but he explains how the various components of song creation emerge and converge with particular songs and different projects. Wheel works with the larger canvas of the album, conceptualizing the songwriting process as both driving and serving successive album concepts.